2015
DOI: 10.1534/g3.115.017699
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response to Acute Thermal Exposure in Juvenile Chinook Salmon Determined by RNAseq

Abstract: Thermal exposure is a serious and growing challenge facing fish species worldwide. Chinook salmon (Oncorhynchus tshawytscha) living in the southern portion of their native range are particularly likely to encounter warmer water due to a confluence of factors. River alterations have increased the likelihood that juveniles will be exposed to warm water temperatures during their freshwater life stage, which can negatively impact survival, growth, and development and pose a threat to dwindling salmon populations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 180 publications
(161 reference statements)
10
56
2
Order By: Relevance
“…Results from our pathway analysis are consistent with this mechanism of misfolded protein removal under thermal stress. Corresponding with our results, previous reports in Oncorhynchus tshawytscha and Stylophora pistillata suggest that the genes involved in protein processing in endoplasmic reticulum are significantly up-regulated under heat stress (Maor-Landaw et al, 2014;Tomalty et al, 2015). Thus, our transcriptomic study indicated that protein processing in endoplasmic reticulum may be involved in thermal stress response in the Hong Kong oysters which are vital for survival of the organism in such unfavorable conditions.…”
Section: Go and Signaling Pathway Enrichment Analysis Of Degssupporting
confidence: 90%
“…Results from our pathway analysis are consistent with this mechanism of misfolded protein removal under thermal stress. Corresponding with our results, previous reports in Oncorhynchus tshawytscha and Stylophora pistillata suggest that the genes involved in protein processing in endoplasmic reticulum are significantly up-regulated under heat stress (Maor-Landaw et al, 2014;Tomalty et al, 2015). Thus, our transcriptomic study indicated that protein processing in endoplasmic reticulum may be involved in thermal stress response in the Hong Kong oysters which are vital for survival of the organism in such unfavorable conditions.…”
Section: Go and Signaling Pathway Enrichment Analysis Of Degssupporting
confidence: 90%
“…The three thermotolerance QTL that explained the greatest percentage of phenotypic variation were found to contain a gene previously associated with thermotolerance in Chinook salmon as well as other species (HSP70) (Narum & Campbell ; Tomalty et al . ) and its inhibitor (BAG) (Takayama et al . ), as well as a gene recently shown to be involved in the MAPK signalling pathway which is involved in thermotolerance (ZNF416) (Dorion & Landry ; Van Rossom et al .…”
Section: Resultsmentioning
confidence: 99%
“…High water temperature can alter expression of genes involved in extracellular matrix and cytoskeleton restructuring, and collagen stabilization in fishes (Jeffries et al, 2012a;Liu et al, 2013;Tomalty et al, 2015), processes that are critical during skeletal growth (Vieira et al, 2013) and were impacted in the present study. Because the larval stages of development in fishes are plastic, temperature impacts during early life stages may lead to long-term effects on growth (Johnston, 2006).…”
Section: Common Transcriptome-wide Responsesmentioning
confidence: 68%